Investigating the Impact of Professional Development Involving Collaborative Action Research on Teachers' Practices - Saquer, Sumaya (Curtin University, 2024)
This study investigated whether collaborative action research as professional development enhances teacher competence for English language teachers in the United Arab Emirates. Using a qualitative, multiple-case study design with twenty female teachers from four public schools, it found that collective participation, coherence, focus, active learning, and sustained duration were key to effective professional growth. Senior management support was crucial. The study demonstrated positive changes in teachers' practices, emphasising teacher leadership and collaboration in educational reforms.